Enhancing Cybersecurity: A Study on Blockchain Technology Applications - Amit Kumar Vyas (International Journal of Intelligent Systems and Applications in Engineering, 2024)
As cyber threats become increasingly sophisticated, traditional cybersecurity measures are proving inadequate to protect sensitive data and systems. Blockchain technology, with its decentralized, immutable, and transparent characteristics, presents a promising solution for enhancing cybersecurity. This paper explores the applications of blockchain technology in various cybersecurity domains, including data integrity, identity management, secure transactions, and secure data sharing. Through a comprehensive review of current literature, theoretical frameworks, and practical case studies, this study examines the efficacy of blockchain in addressing contemporary cybersecurity challenges. The findings indicate that while blockchain technology offers significant advantages, its integration into existing cybersecurity frameworks is not without challenges, necessitating further research and development to realize its full potential.